Dietary vitamin K intake associates with reduced all-cause mortality in non-alcoholic fatty liver disease patients - Yu Huang; Xianfeng Zhu; Liang Han; Hulan Hu (Scientific Reports)
Abstract This study aimed to investigate the association between dietary vitamin K intake and all-cause mortality in individuals with non-alcoholic fatty liver disease (NAFLD). We analyzed data from 7857 NAFLD participants in the National Health and Nutrition Examination Survey (NHANES 2005–2018) linked to mortality outcomes from the National Death Index (NDI). Dietary vitamin K intake was log-transformed (ln[VK]) for analysis. Multivariable Cox proportional hazards models and restricted cubic splines were used to evaluate dose-response relationships. Sensitivity analyses, subgroup analyses, and receiver operating characteristic (ROC) curves were performed to validate findings. Over 180 months of follow-up, 842 deaths occurred. Higher ln[VK] was associated with reduced mortality risk, demonstrating an adjusted hazard ratio (HR) of 0.81 per 1-unit increasement (95% confidence interval CI 0.67–0.98, P-trend = 0.028). Restricted cubic splines revealed a U-shaped relationship (P-nonlinear = 0.0009), with an optimal threshold at 121 µg/day (ln[VK] = 4.71). Below this threshold, each unit increase in ln[VK] corresponded to a 33% lower mortality risk (HR = 0.67; 95% CI 0.55–0.81), whereas no significant association was observed above it (HR 1.07; 95% CI 0.67–1.71). The fully adjusted prediction model showed robust discriminative ability, with an area under the curve (AUC) of 0.832. Results remained consistent across sensitivity analyses. Moderate dietary vitamin K intake (up to 121 µg/day) is associated with reduced all-cause mortality in NAFLD patients, with a threshold effect informing tailored dietary recommendations. This study provides novel evidence for optimizing vitamin K intake in NAFLD management.